Academic Senate Minutes 2003-04-01 - Academic Senate:::::::::
Agenda approved. Minutes delayed. Potential Emeritus Faculty from '02-03 – approved. S. Jones provided follow up information to the Budget Summit. Resolution to Assess Faculty confidence in the Academic Senate and SSU Administration failed. Grants and Contracts Policy approved. Changes in the Chemistry Major approved. Lobbying and Use of Appropriated Federal Funds policy – First Reading. Policy on Copyright Ownership – First Reading.